Alterações centrais e periféricas em diferentes modelos de dor pulpar em ratos - Filippini, Helena Fetter (2017)
The central and peripheral mechanisms involved in pulpal pain are still unclear. This study compared, initially, the chronic pulpitis model evoked by the application of complete Freund's adjuvant (CFA) into the pulps of rats, with other models of pulpitis. For this purpose, the pulps of the left upper first molars of Wistar rats were accessed. There were four experimental groups according to the surgical procedure: open, closed, CFA and naïve. Behavioral changes, as well as, body weight gain and food and water consumption, were evaluated at different experimental times (1, 2, 3 and 8 days). After euthanasia, blood, brain and trigeminal ganglion (TG) samples were collected for further analysis. All experimental groups with pulp acess had a decrease in body weight gain (for up to 3 days). A reduction in food consumption was observed in all the groups with pulp exposure, on the first day. The CFA group showed a significant reduction of locomotor activity (at 1 and 3 days), which was associated with increased satellite glial cells activation in the ipsilateral TG. Activation of astrocytes in the amygdala was not affected in the studied groups. The second part of this study investigated the relevance of Toll-like receptor 4 (TLR4) activation in the acute pulpitis caused by the application of the transient receptor potential ankyrin-1 (TRPA1) mustard oil (MO), into the rat pulps. Preliminary studies were performed to compare the sensorimotor activity of the masticatory muscles with the application of lipopolysaccharide (LPS) or MO in the dental pulp. The model using MO application into the pulp of rats was selected, because of the marked increase of the electromyographic activities evoked by this agent, when compared to LPS. The animals received a intrathecal (i.t.) pre-treatment with the TLR4 LPS-RS antagonist (25 μg / 10 μl) or saline solution (10 μl) (vehicle group), 10 min before pulp application of MO. For this purpose, a stereotaxic surgery was performed to access the trigeminal subnucleus caudalis. Changes in electromyography activity (EMG) of masticatory muscles were recorded for 15 min after the MO application into the pulp. The trigeminal caudalis subnucleus was removed after euthanasia, for evaluation of TLR4 expression by western blotting analysis. Changes in EMG activity in anterior digastric muscles were significantly reduced by the intrathecal administration of LPS-RS in the trigeminal subnucleus caudalis (p ˂0.05). The data obtained suggest the participation of satellite glial cells in the chronic pulpitis model induced by CFA, as well as, TLR4 receptors in the acute pulpitis model caused by MO application into the rat pulps. Altogether, the present results shed new light on the mechanisms underlying acute and chronic tooth pulp inflammatory pain.